2020
DOI: 10.15407/ujpe65.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition in Dilute Solutions of Rod-Like Macromolecules

Abstract: On the basis of experimental data obtained for the viscosity in aqueous solutions of hydroxypropyl methylcellulose (metolose), it has been found that a structural transition takes place in dilute solutions of rod-like macromolecules with the increasing temperature. Namely, macromolecules form clusters in which they are arranged in parallel to one another. It is shown that this transition is a set of local phase transitions of the first kind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Let us determine the shape that a polymer cluster has at 𝑇 = 50 ∘ C. In work [7], on the basis of viscometric experiments, it was found that, at this temperature, metolose clusters have the form of elongated ellipsoids of rotation, for which the ratio between the lengths of the axes equals…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let us determine the shape that a polymer cluster has at 𝑇 = 50 ∘ C. In work [7], on the basis of viscometric experiments, it was found that, at this temperature, metolose clusters have the form of elongated ellipsoids of rotation, for which the ratio between the lengths of the axes equals…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…So, what does the network in rigid-chain polymers look like, and what is the mechanism of its formation? To answer these questions, we studied the aqueous solutions of rigid-chain polymers [6][7][8][9][10][11][12][13]. As the research object, typical representatives of the polymers belonging to this class, cellulose derivatives, were chosen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the mechanism of gelation has not been studied enough yet despite the existence of a number of relevant hypotheses (see, e.g., works [10][11][12][13]). Earlier, we studied the thermally induced change in the macromolecular conformation of cellulose derivatives in highly dilute aqueous solutions [14,15]. It was shown that the examined sol-gel transition in those systems has a character typical of the phase transition of the first kind.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight of this compound equals 10 5 , and the substitution degree is 75.7%. We have already studied earlier the features of the sol-gel transition in aqueous solutions of cellulose derivatives, both experimentally [20,21] and using a mathematical simulation [22]. It was shown that the researched sol-gel transition in those systems has a character of the firstkind phase transition.…”
Section: Experimental Partmentioning
confidence: 99%